My Boy - Austin, Albert; Heerman, Victor; MacWilliams, Glen; Martin, Robert; Coogan, Jackie; Brundage, Mathilde; Gillingwater, Claude (Warner, 2003)
Jackie Blair (Jackie Coogan) is an orphan, his mother dying aboard the ship that is bringing the two to America, and when he reaches Ellis Island it is determined that he will be deported back to Europe. Captain Hicks (Claude Gillingwater), an out of work old salt, visiting a friend at immigration, offers Jackie a friendly gesture. Jackie gets free from immigration, and not knowing anyone in the big city, adopts the old man, following him home. Captain Hicks agrees that Jackie can stay with him one night, but then he’s going back to the immigration officials ... [digitalsilents.com]
Keywords: DVD-Video